Broadening the photoresponsive activity of anatase titanium dioxide particles via decoration with partial gold shells - Orawan Khantamat (2018)
© 2017 Elsevier Inc. Titanium dioxide (TiO2) has gained increasing interest in materials research due to its outstanding properties and promising applications in a wide range of fields. From this perspective, we report the synthesis of custom-designed anatase TiO2submicrometer particles coated with partial Au shells (ATiO2-AuShl). The synthetic strategy used herein yields uniformly shaped monodisperse particles. Amorphous TiO2core particles were synthesized using template-free oxidation and hydrolysis of titanium nitride (TiN); subsequent hydrothermal treatment generated anatase TiO2(ATiO2) particles. Coating ATiO2particles with partial Au shells was accomplished using a simple seeded-growth method. Evaluation of the optical properties of these ATiO2-AuShl particles showed that these submicrometer composites exhibited an intense absorption peak for TiO2in the UV region (∼326 nm) and a broad extinction band in the visible range (∼650 nm) arising from the incomplete Au shell. These ATiO2-AuShl composite particles provide a unique and effective means for broadening the optical response of TiO2-based nano- and micron-scale materials. The simplicity of our synthetic method should broaden the application of ATiO2-AuShl particles in various visible light-driven technologies.